Using bioinformatics for the identification of key peptides to engineer dopamine neurons. Towards a therapy for Parkinson’s disease. - Mitchell, William D; Orme, Rowan P; Hart, Sarah R; Fricker, Rosemary A (PeerJ Preprints, 2018)
Parkinson’s disease is a widespread condition caused by degeneration of dopamine neurons in the midbrain. A number of proteins are known to be important to signalling mechanisms present in the midbrain during natural dopamine neuron development, and may be utilised to better produce dopamine neurons in vitro. Relative expression levels of proteins were obtained from substantia nigra tissue of rats from embryonic days E11 through E14 using isobaric tagging for relative and absolute quantification. This project analysed the dataset obtained, with an emphasis on relative expression levels of proteins across the four-day period. Bioinformatics searching of online databases reduced the dataset from 3325 proteins to a shortlist of five worthy of further investigation. It is hoped that the proteins identified using these techniques will help to refine protocols for the production of dopamine neurons in vitro.
Keywords: Proteomics; iTRAQ; Dopamine neuron; Stem cells; Neural development; Parkinson’s disease; Bioinformatics